Visitasi Akreditasi Sekolah untuk Pembinaan, Pengembangan, dan Peningkatan Mutu Madrasah di MIS Miftahul Aula - Riyadi, Slamet (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Accreditation is an activity to assess the feasibility of basic and secondary education units, and early childhood education and non-formal education units based on established criteria to provide quality assurance of education. Accreditation is useful as a reference in efforts to improve the quality and development of schools/madrasas. The method used for this accreditation visitation refers to the 2020 Education Unit Accreditation Instrument (IASP 2020). put emphasis on IASP2020 on measuring performance indicators with 4 main components, namely the quality of graduates, the ongoing learning process in schools/madrasas. This visitation was carried out for 2 days from 05 August 2022 to. August 6, 2022, at MIS Miftahul Aula, Jl. Husin Hamzah RT.05, Sebuai, Kec. Kumai, Kab. Kotawaringin Barat Prov. Central Kalimantan. Visitation activities are carried out through field observations, class observations, and interviews with madrasa residents in the context of verification, as well as validation of data and information provided by madrasah through accreditation instruments. After knowing the items that have a low score, suggestions and recommendations are prepared. These suggestions are in the framework of fostering, developing and improving the quality of schools/madrasah.